1980
DOI: 10.1007/bf01561564
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of human Ia antigens coded for by a gene locus closely linked toHLA-DR locus

Abstract: Human Ia(-like) specificities controlled by gene loci other than HLA-DR were searched for at the molecular level in cells of human B-cell-type cell lines which carry two established DR specificities. Chevalier cells of DRw3 and 7 and U698M cells of DRw2 and 4 were used. Their Ia molecules were partially purified, radioiodinated and analyzed for Ia specificities by the direct binding and sequential binding assays with a selected panel of human Ia alloantisera. It was possible in both the cell lines to define a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…One well known segregant series was defined during the Seventh and Eighth International Histocompatibility Workshops and includes HLA-DR1 through HLA-DRw10 (2,3). In addition, several other class II antigenic serological specificities have been described by different nomenclatures, such as MB, MT, DC, or BR (4)(5)(6)(7).…”
Section: Dr5mentioning
confidence: 99%
“…One well known segregant series was defined during the Seventh and Eighth International Histocompatibility Workshops and includes HLA-DR1 through HLA-DRw10 (2,3). In addition, several other class II antigenic serological specificities have been described by different nomenclatures, such as MB, MT, DC, or BR (4)(5)(6)(7).…”
Section: Dr5mentioning
confidence: 99%
“…Molecules that express these alloantigenic determinants are known as class II or human Ia molecules. The HLA-DR antigenic system, which is highly polymorphic, can be distinguished from the others on the basis of immunodepletion (1)(2)(3), capping studies (4), and two-dimensional (2-D) gel analysis (5). Similarly, SB defines a distinct alloantigenic system on the basis of detection by primed lymphocytes and a genetic location distinct from and centromeric to HLA-DR (6).…”
mentioning
confidence: 99%
“…Therefore, the reactivity of the above monoclonals is not restricted to the Ia supertypic specificities described up to now [3,4]. Moreover, comparison of peptic digests of NG1 and NG2 Ia subsets analyzed by two-dimensional peptide mapping has indicated that the two subsets display significant structural differences [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular pool consists of distinct subsets of molecules which can be detected by specific antisera. Thus, it has been possible to identify Ia subsets clearly distinct from the classical HLA-DR molecules apparently expressed only in individuals with a given HLA-DR phenotype [3,4]. In addition, other Ia subsets have been identified which are present in all individuals, irrespective of their HLA-DR phenotype; they have been named Ia isotypes [5,61.…”
Section: Introductionmentioning
confidence: 99%